2003
DOI: 10.1046/j.1523-1755.2003.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired K+ regulation contributes to exercise limitation in end-stage renal failure

Abstract: Patients with ESRF exhibit grossly impaired extrarenal K+ regulation during exercise, demonstrated by an excessive rise in PK relative to work performed. We further show that K+ regulation during exercise was correlated with aerobic exercise performance. These results suggest that disturbed K+ regulation in ESRF contributes to early muscle fatigue during exercise, thus causing reduced exercise performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
4
20
0
2
Order By: Relevance
“…Disturbances in muscle K ϩ homeostasis also have been linked with muscular fatigue (19). Together with a more recent study demonstrating a relatively higher plasma K ϩ rise with exercise in hemodialysis patients (18), this suggests that abnormalities in muscle K ϩ regulation may be a factor that limits exercise performance. Although the patients in this study Histologic muscle changes that are found in CKD also may influence muscle function.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Disturbances in muscle K ϩ homeostasis also have been linked with muscular fatigue (19). Together with a more recent study demonstrating a relatively higher plasma K ϩ rise with exercise in hemodialysis patients (18), this suggests that abnormalities in muscle K ϩ regulation may be a factor that limits exercise performance. Although the patients in this study Histologic muscle changes that are found in CKD also may influence muscle function.…”
Section: Discussionmentioning
confidence: 96%
“…We also previously found impaired potassium (K ϩ ) regulation during exercise in hemodialysis patients compared with healthy control subjects (18). Because muscle K ϩ disturbances are linked with muscle fatigue (19), this was suggested to contribute to reduced exercise capacity in hemodialysis patients (18 (15).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This deficient mitochondrial energy metabolism means that the rate of production of high energy organophosphorus compounds (ATP and PCr) following exercise is impaired, leading to slower functional recovery from a bout of muscle contraction. These patients also have increased lipid peroxidation (an indicator of increased production of toxic free radicals from mitochondria) [31], lower levels of muscle total carnitine, which is a cofactor for the transport of long-chain fatty acid fuels into the mitochondria [32], and impaired extrarenal potassium regulation which may contribute to early muscle fatigue during exercise [33]. …”
Section: Factors Leading To Poor Physical Function In Ckdmentioning
confidence: 99%
“…Otra debilidad fue no controlar parámetros fisioló-gicos, de composición corporal o bioquímicos, como lo han hecho otros estudios 41,31 . Por lo que no se puede saber si este programa, además de generar efectos positivos en los parámetros estudiados, puede generar beneficios a nivel celular, bioquímico o muscular o, por el contrario, generar efectos negativos, como un aumento en la concentración plasmática de K+ post-ejercicio, factor ya observado en estudios previos que contribuiría a una rápida fatiga muscular 42 . En este sentido, se recomiendan estudios más amplios y con un mejor diseño metodológico que permitan determinar la efectividad de este tipo de programas de ejercicio en pacientes con ERC.…”
Section: Discussionunclassified